MORPHOMETRICAL CHANGES IN THE RATS UTERUS THICKNESS AFTER 30 DAYS OF HEAVY METAL SALTS EXPOSURE - Kateryna Sikora (Eastern Ukrainian Medical Journal, 2022)
Introduction. Much attention is paid to the global ecological problem of environmental pollution with heavy metals (HM), starting from their production and use and ending with the search for means of their degassing and bioremediation. Particular attention is drawn to the study of the influence of HM on the reproductive system, in particular, the uterus. This is due to the high risk of reproductive ability deterioration and the reflection of the consequences of HM exposure in future generations. Objective. The objective of our study was to perform morphometric measurement of the structural elements of the uterine wall in female rats under the conditions of 30-day exposure to HM salts, as well as to study the protective role of vitamin E. Materials and Methods. For the experimental study, 24 female rats were selected and randomly divided into three series (8 rats in each): series I included control rats that received ordinary drinking water; series II included rats that daily consumed water saturated with HM salts; and series III included rats that were administered vitamin E orally every day against the background of constant consumption of water enriched with a combination of HM. After 30 days of the experiment, the uteri were removed; the sections were stained with hematoxylin and eosin for microscopic examination, followed by morphometric measurement of the structural elements and their statistical analysis. Results. First, we measured the morphometric dimensions of the structural elements of the uterine wall in the control animals. At the same time, in the animals of the experimental series II and III, the morphometric indicators underwent significant changes. Thus, on the 30th day of the study, series II rats showed a significant thickening of the uterine wall by 31.03% (p < 0.001) vs. the indicators of the control series. A similar trend of morphometric changes in the thickness of the uterus was noted in series III animals, where the uterus thickened by 20.58% (p < 0.001). Moreover, a significant difference was also observed between experimental series II and III. The analysis of the organ structural components in the experimental series indicated the predominance of endometrium thickness over myometrium thickness. Сonclusions. The results showed that 30-day exposure to HM led to a statistically significant thickening of the uterine wall. At the same time, the most pronounced changes in morphometric indicators were observed in the endometrium (in comparison with the myometrium and perimetrium) of both experimental models, both under the conditions of HM combination exposure and during the prophylactic use of vitamin E against the background of the action of xenobiotics. It is important to note that with the use of vitamin E, the morphometric indicators of the uterine thickness were characterized by a less pronounced transformation of values, although they still significantly exceeded the values of the control series.